Student profiling on university co-curriculum activities using data visualization tools - Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (IP Publishing LLC, 2017)
Co-curricular activities are playing a vital role in the development of a holistic student.Co curriculum can be described as an extension of the formal learning experiences in a course or academic program.There are many co-curriculum activities such as students’ participation in sports, volunteerism, leadership,entrepreneurship, uniform body, student council, and other social events.The number of student involves in co-curriculum activities are large, thus creating an enormous volume of data including their demographic facts, academic performance and co-curriculum types. The task for discovering and analyzing these information becomes increasingly difficult and hard to comprehend.Data visualization offer a better ways in handling with large volume of information.The need for an understanding of these various co-curriculum activities and their effect towards student performance are essential. Visualizing these information can help related stakeholders to become aware of hidden and interesting information from large amount of data drowning in their student data.The main objective of this study is to provide a clearer understanding of the different trends hidden in the student co-curriculum activities data with related to their activities and academic performances.The data visualization software was used to help visualize the data extracted from the database.